Mangrove condition at a marine conservation area at Moramo Bay, Sulawesi, Indonesia - DEDY OETAMA; LUCHMAN HAKIM; TRI D. LELONO; MUHAMMAD MUSA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Oetama D, Hakim L, Lelono TD, Musa M. 2023. Mangrove condition at a marine conservation area at Moramo Bay, Sulawesi, Indonesia. Biodiversitas 24: 6536-6544. The mangrove ecosystem is one ecosystem that supports biodiversity at the Marine Conservation Area (MCA) in Moramo Bay, Southeast Sulawesi, Indonesia. The area of the mangrove ecosystem in Moramo Bay is approximately 1,933.09 hectares, with an MCA of 1,281.46 hectares. This ecosystem plays an important role in protecting the coastline from erosion due to the seawater filtration process in the bay. This study aims to provide information regarding the status of mangrove ecosystem in the MCA, including species, density, basal area, dominance, and canopy cover percentage, which was used to state the standard criteria for mangrove ecosystem damage. The methods involved a 10×10 m² transect and hemispherical photography using a fisheye lens with a 180° field of view. Seven species of mangrove were found in Moramo Bay MCA, including Bruguiera gymnorrhiza (L.) Lam. (dominating with a basal area value of 136,963.66), followed by Sonneratia alba Sm. (153,111.90), Rhizophora mucronata Lam. (113,708.04), Rhizophora stylosa Griffith (28,869.95), Xylocarpus moluccensis (Lam.) M.Roem. (9,326.59), Avicennia marina (Forssk.) Vierh. (3,419.46), and Rhizophora apiculata Blume with a basal area value of 1,690.11. The density of mangrove vegetation was in the criteria of rare to dense, with approximately 800-4,200 individuals per hectare. Furthermore, the mangrove ecosystem in the MCA was found to be damaged up to good condition, with canopy cover percentage values of 45.85%-98.88%. The condition of the mangrove ecosystem in Moramo Bay MCA preserves a basic deliberation for the Indonesian government for adaptive and sustainable management of conservation areas. Protection, preservation, and utilization of mangrove ecosystems should be maximized in all coastal areas to improve the quality of biodiversity.